Correlation Between Learning Interest, Learning Environment, and Academic Achievement in History Learning - Berlian Ayu Pertiwi; Fahruddin Fahruddin (Indonesian Journal of History Education, 2024)
This study aims to determine the level of student interest in learning, the quality of the learning environment, the level of achievement in learning history, the impact of interest in learning on achievement, the influence of the learning environment on historical achievement, the relationship between interest in learning, and the learning environment on historical achievement. A quantitative survey approach was employed, with data collected through questionnaires and report card records. The results indicate that interest in learning history was rated at 76.75% (good), the quality of the learning environment at 83.20% (excellent), and historical learning achievement at 83.10% (particularly good). The correlation between interest in learning and historical achievement was positive but weak (0.124), while a positive, moderate, and significant influence was observed between the learning environment and historical achievement (correlation 0.229). A low, positive, but statistically insignificant relationship (0.232) was found between combined interest in learning and the learning environment on historical achievement. This study provides empirical contributions in history learning, encouraging principals and teachers to improve students' learning interests and ensure a good learning environment for high achievement.